Utilization of Cassava Rich in Insoluble Fiber as an Alternative Prebiotic to Increase Family Immunity in Nagari Katapiang, Batang Anai District, Padang Pariaman Regency - Melindra Mulia; Umar Kalmar Nizar; Desy Kurniawati; Fauzana Gazali (Pelita Eksakta, 2021)
Cassava is widely available, even abundant in the Katapiang Urban Village, Batang Anai Sub-district. Unfortunately, society does not know the benefits of cassava as a prebiotic that is beneficial for family health. This community service activity aims to increase knowledge about prebiotics from cassava and how to process them so that it is beneficial to society. In this way, the health of the family can be maintained. The activity was carried out at the Masjid Istiqomah, Katapiang Urban Village, Batang Anai Sub-district, Padang Pariaman District, involving 18 targets. The activities implementation is divided into two stages, namely guided and independent activities. In the guided activities, interactive counseling and practical methods are used. Meanwhile, in independent activities, the targets made spice drinks in groups. The results of the activity showed targets’ knowledge about prebiotics and how to process cassava had increased so that they can get optimal benefits for health. The target is also interested in producing and consuming, their own processed cassava that has been made.